Aflatoxin M1 in milk by immunoaffinity column cleanup with TLC/HPLC determination - Shundo,Luzia (2006)
During 2002 and 2003, a total of 107 samples of raw, pasteurized and ultrahigh treated temperature (UHT) milk commercialized in the cities of São Paulo and Marília (SP) were analyzed for the presence of aflatoxin M1 (AFM1). AFM1 was detected in 79 (73.8%) of milk samples, ranging from <0.02 to 0.26 mug/L.The samples were analyzed using an immunoaffinity column for cleanup and a thin layer chromatography for determining AFM1. The parameters, such as recovery, repeatibility, detection and quantification limit were evaluated to optimize this method (in-house). Based on spiked samples, the recovery values ranged from 85.83 to 73.86% at levels of 0.010-0.50 mug/L, respectively, and the relative standard deviation for repeatibility ranged from 7.73 to 2.08%. The quantification limit was 0.02 mug/L. The results of some samples analyzed by this method demonstrated a satisfatory correlation when compared with High Performance Liquid Chromatography (HPLC). In conclusion, immunoaffinity column cleanup gave excellent results for recovery, sensibility and sample through put. Despite the high rate of occurrence of AFM1 in samples in both cities, the contamination level could not be considered a serious public health hazard, according to Brazilian legislation.